KAJIAN YURIDIS TERHADAP WANPRESTASI YANG DILAKUKAN PEMEGANG KARTU KEPADA PENERBIT DALAM PERJANJIAN KARTU KREDIT - Intan Trinawangsih, I Gusti Ayu; Sekar, Dewa Nyoman (Kertha Semaya : Journal Ilmu Hukum, 2013)
This paper entitled “Legal Consequence about Wanprestasi that Cardholder Does to Issuer in Credit Card Agreement”. This paper uses normative juridical methods and the statute approach. Financial institution appears is needed in attempt to grow the economic up. One of financial institution activity is credit card business. Issuer to do its activity based to a standard contract that made by issuer as a creditor and for the next step agreed and signed by expectant cardholder as debtor. As credit to be given, there must be risks even based by standard contract. Problem that often comes up in credit cards issuance is wanprestasi that cardholder does.
Keywords: Cardholder, Issuer, Wanprestasi, Credit Card Agreement